2003
DOI: 10.1021/cm0207494
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite and Pyrochlore Modifications of Pb2MnReO6:  Synthesis, Structure, and Electronic Properties

Abstract: We describe the synthesis and investigations of Pb 2 MnReO 6 in perovskite and pyrochlore modifications. Both the modifications are formed at atmospheric pressure, the perovskite (I) at 550°C and the pyrochlore (II) at 600°C. Rietveld refinements of the structures using the powder XRD data show that oxide I adopts the monoclinic (P2 1 /n) double perovskite structure with partial ordering (∼72%) of Mn II /Re VI at the octahedral sites, while oxide II crystallizes in a defect-pyrochlore structure where Mn II /Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 32 publications
3
27
0
Order By: Relevance
“…The observed effective moments (µ eff / mol Co) and temperature-axis intercepts (θ, K) were obtained from linear fits of the inverse susceptibility data in the temperature range 100-300 K. not unexpected given the triangular symmetry of the metal lattices which results in geometric magnetic frustration. [49][50] Pyrochlore compounds are known to exhibit a wide range of cooperative magnetic properties and, for example, are of significant interest as "spin-ice" systems. [51][52][53] …”
Section: Magnetic Properties Of Pyrochlore Phasesmentioning
confidence: 99%
“…The observed effective moments (µ eff / mol Co) and temperature-axis intercepts (θ, K) were obtained from linear fits of the inverse susceptibility data in the temperature range 100-300 K. not unexpected given the triangular symmetry of the metal lattices which results in geometric magnetic frustration. [49][50] Pyrochlore compounds are known to exhibit a wide range of cooperative magnetic properties and, for example, are of significant interest as "spin-ice" systems. [51][52][53] …”
Section: Magnetic Properties Of Pyrochlore Phasesmentioning
confidence: 99%
“…For La containing compositions, best Rietveld fit were obtained when La was disordered at both Bi(1) and Bi (2) Atom Position Our efforts to synthesize Bi 3 MnSb 2 O 11 and Bi 3 NiSb 2 O 11 in KSbO 3 type structure were unsuccessful. Instead, pyrochlore phases (Ramesha et al 2003a, b) were obtained as revealed from their powder XRD patterns. The formation of pyrochlore phase implies that Mn is in +2 oxidation state (instead of +3) corresponding to the chemical formula, Bi 2 Mn 0·67 Sb 1·33 O 7 .…”
Section: Photodegradation Experimentsmentioning
confidence: 99%
“…Another member of the Pb 2 MReO 6 series, e.g. Pb 2 MnReO 6 , was also studied 24 . This double perovskite crystallized with monoclinic symmetry (S. G. P2 1 /n) and shows a T C ∼ 100 K and semiconducting properties.…”
Section: Introductionmentioning
confidence: 99%